Kolaborasi Stakeholder dalam Penanganan Bencana Kebakaran di Kota Surabaya: Perspektif Pentahelix - Paulyna, Anita; Glorino Rumambo Pandin, Moses; Soemartono Waloejo, Christrijogo (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The high population density in Surabaya City creates challenges for firefighters responding to fires, necessitating effective stakeholder collaboration. While the pentahelix concept has been identified in research as a promising approach to improve service delivery, it has not yet been implemented in Surabaya's fire management. This qualitative descriptive evaluative study analyzed weaknesses in stakeholder collaboration and assessed economic and community welfare impacts of fire disasters. The research involved 14 informants selected through purposive sampling, with data collected via interviews and documentation, and analyzed using three-stage coding. Results revealed suboptimal stakeholder collaboration due to several factors: inadequate implementation of health protocols, insufficient citizen safety equipment, neglected fire-prone areas, traffic congestion, disorganized residential facilities, and limited fire engine availability. The economic and welfare impacts included income and job losses, alongside psychological trauma among fire victims. The study recommends that the Fire and Disaster Management Agency (DPKP) strengthen collaborative efforts through clearer authority distribution and appropriate budgeting to meet disaster management requirements, ultimately fostering more effective collaboration among stakeholders.